When two anomalies meet: Volume and timing effects on earnings announcements - Hu, Wei; Wong, Mark; Cheung, Adrian Wai Kong (Wiley-Blackwell, 2020)
This study investigates the joint effect of trade volume and report timing on earnings‐announcement premiums. We find that high trading volume effect adds to early announcement effect but not vice versa. After controlling for firm characteristics, late timing and high trade volume have a positive joint effect; stocks with late announcements and low trade volume earn the largest but short‐lived premium. We cannot find evidence to support the notion that early announcements result in superior premiums; the unusual volume effect is much greater in magnitude, longevity, and significance than the timing effect.